Amorphous MoS2 coated Ni3S2 nanosheets as bifunctional electrocatalysts for high-efficiency overall water splitting. (1st February 2020) - Song, Shiwei; Wang, Yanhui; Li, Wei; Tian, Pengfei; Zhou, Shuyu; Gao, Hongwei; Tian, Xueqing; Zang, Jianbing
Abstract: Efficient non-noble metals bifunctional electrocatalysts play a significant role in both hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) for overall water splitting. Herein, amorphous MoS2 (a-MoS2 ) coated Ni3 S2 with three-dimensional nanosheets composite architecture supported on nickel foam (a-MoS2 -Ni3 S2 /NF) was prepared via hydrothermal vulcanization Ni(OH)2 /NF using thiourea and sodium molybdate dihydrate. In this process, the network structure of Ni3 S2 nanosheets was primarily formed by in situ vulcanization of the Ni(OH)2 on nickel foam (NF) and was covered by the amorphous MoS2 (a-MoS2 ) nanoflakes as a skeleton at the same time. Not only did the hierarchical nanosheets nanoarrays and self-supported composite architecture of a-MoS2 -Ni3 S2 /NF prevent the accumulation of nanoflakes, increase the active surface area and expose more active sites, but also facilitated the penetration of electrolytes and the transfer of charge/mass. Meanwhile, the synergistic effect between the a-MoS2 nanoflakes with highly disordered structure and Ni3 S2 substrates with high conductivity significantly enhanced the HER and OER activity. The nanosheets composite structure of a-MoS2 -Ni3 S2 /NF demonstrated an extremely low overpotential of 81 at 10 mA cm −2 for HER and 150 mV at 100 mA cm −2 for OER in alkaline conditions, respectively. In particular, when taken as both positive and negative electrodes to the full water electrolysis under alkaline medium, the bifunctional electrocatalyst of a-MoS2 -Ni3 S2 /NF only required the battery voltage of 1.54 V at 100 mA cm −2 . Graphical abstract: Image 1 Highlights: Amorphous MoS2 coated Ni3 S2 on NF was prepared via hydrothermal vulcanization. a-MoS2 -Ni3 S2 /NF displayed a 3D composite nanosheets self-supported architecture. There is a synergistic effect between a-MoS2 nanoflakes and Ni3 S2 substrates. The 3D structure can prevent nanoflakes stack and promote charge/mass transfer. a-MoS2 -Ni3 S2 /NF shows a cell voltage of 1.54 V at 100 mA cm −2 for water splitting.